2021
DOI: 10.1093/neuonc/noab301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dose, volume, and outcome in children with localized, intracranial ependymoma treated with proton therapy within the prospective KiProReg Study

Abstract: Purpose Radiotherapy (RT) of ependymoma in children is an important part of the interdisciplinary treatment concept. However, feasibility and dose concepts are still under investigation, particularly in very young children. The aim of this study was to evaluate standard dose and volume of proton therapy (PT) in children with ependymoma. Material and Methods In this analysis, 105 patients with localized, intracranial ependymom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…9 Non-randomised PBT studies for 95 localised paediatric ependymoma have shown comparable disease outcomes to photon irradiation. [10][11][12] In the largest series to date reporting the long-term outcomes of PBT for 386 paediatric patients with ependymoma, the 7-year local control and overall survival rates were 77% and 82.2%, respectively. 10 Currently, there is no randomised evidence comparing PBT with photon irradiation for paediatric ependymomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Non-randomised PBT studies for 95 localised paediatric ependymoma have shown comparable disease outcomes to photon irradiation. [10][11][12] In the largest series to date reporting the long-term outcomes of PBT for 386 paediatric patients with ependymoma, the 7-year local control and overall survival rates were 77% and 82.2%, respectively. 10 Currently, there is no randomised evidence comparing PBT with photon irradiation for paediatric ependymomas.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment for paediatric patients with intracranial ependymomas of WHO grade 2/3 is maximal safe resection followed by local radiation therapy 9 . Non‐randomised PBT studies for localised paediatric ependymoma have shown comparable disease outcomes to photon irradiation 10–12 . In the largest series to date reporting the long‐term outcomes of PBT for 386 paediatric patients with ependymoma, the 7‐year local control and overall survival rates were 77% and 82.2%, respectively 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Methods of treatment and data collection have been previously published [ 15 ]. Face-to-face FU consultations with a radiation oncologist were scheduled after three months and annually thereafter at our center.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, disease itself can lead to neurocognitive symptoms. All of these factors may influence the condition of the child before RT and need to be taken into account for treatment planning as well as dose prescription [ 15 ]. Possibilities for dose reductions need to be considered, but are limited in order not to compromise the aim of high survival outcomes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing SIOP-EP-II will further characterize the safety and efficacy of a stereotactic boost (8 Gy in 2 fractions) to unresected ependymoma (NCT02265770). Proton radiotherapy has also been found to be safe and result in similar outcomes compared to photon radiotherapy [75][76][77]; however, long-term toxicities comparing the two modalities remain limited [78].…”
Section: Ependymomamentioning
confidence: 99%